Rational Design and Self-Assembly of Histidine-Rich Peptides on a Graphite Surface - Luo, Wei (Langmuir : the ACS journal of surfaces and colloids, 2023)
Histidine-rich peptides (HRPs) have been investigated to create functional biomolecules based on the nature of histidine, such as ion binding and catalytic activity. The organization of these HRPs on a solid surface can lead to surface functionalization with the well-known properties of HRPs. However, immobilization of HRPs on the surface has not been realized. Here, we design a series of octapeptides with histidine repeat units, aiming to establish their self-assembly on a graphite surface to produce a highly robust and active nanoscaffold. The new design has (XH)4, and we incorporated various types of hydrophobic amino acids at X in the sequence to facilitate their interaction with the surface. The effect of the pair of amino acids on their self-assembly was investigated by atomic force microscopy. Contact angle measurement revealed that these assemblies functionalized graphite surfaces with different wetting chemistry. Moreover, the secondary structure of peptides was characterized by Fourier transform infrared spectroscopy (FTIR), which gives us further insights into the conformation of histidine repeat peptides on the surface. Our results showed a new approach to applying histidine-rich peptides on the surface and tuning the self-assembly behavior by introducing different counter amino acids that could be integrated with a wide range of biosensing and biotechnology applications